Solvation structure manipulation of ester-based electrolyte by acetonitrile additive enables high-capacity and stable K-storage for phenazine-based anode - Xiaokang Chu; Ran Chen; Hang Chen; Hao Wang; Luanjie Nie; Haobo Xia; Qingxue Lai; Zixia Lin; Mengtao Ma; Hao Gong; Jing Zheng (Chemical Engineering Journal, 2024)

White matter microstructure damage measured by automated fiber quantification correlates with pain symptoms in lung cancer patients - Li Ran; Jiang Liu; Xiaosong Lan; Xiaoyu Zhou; Yong Tan; Jing Zhang; Yu Tang; Lin Tang; Jiuquan Zhang; Daihong Liu (Brain Imaging and Behavior, 2024)

Loss of CHCHD2 Stability Coordinates with C1QBP/CHCHD2/CHCHD10 Complex Impairment to Mediate PD-Linked Mitochondrial Dysfunction - Yan-Lin Ren; Zheng Jiang; Jia-Yi Wang; Qin He; Si-Xu Li; Xiao-Jing Gu; Yang-Ran Qi; Min Zhang; Wen-Jie Yang; Bei Cao; Jing-Yu Li; Yi Wang; et al. (Molecular Neurobiology, 2024)

Electrolyte matching design for carboxylic acid-based organic K-storage anode - Jing Zheng; Hao Wang; Chi Hu; Hang Chen; Wanying Zhang; Xiaokang Chu; Luanjie Nie; Ran Chen; Jianying Long; Meng Lei; Jijian Xu; Zixia Lin; et al. (Chemical Engineering Journal, 2024)

ML-Net: A Multi-Local Perception Network for Healthy and Bleached Coral Image Classification - Sai Wang; Nan-Lin Chen; Yong-Duo Song; Tuan-Tuan Wang; Jing Wen; Tuan-Qi Guo; Hong-Jin Zhang; Ling Mo; Hao-Ran Ma; Lei Xiang (Journal of Marine Science and Engineering, 2024)
Healthy coral reefs provide diverse habitats for marine life, playing a crucial role in marine ecosystems. Coral health is under threat due to global climate change, ocean pollution, and other environmental stressors, leading to coral bleaching. Coral bleaching disrupts the symbiotic relationship between corals and algae, ultimately impacting the entire marine ecosystem. Processing complex underwater images manually is time-consuming and burdensome for marine experts. To rapidly locate and monitor coral health, deep neural networks are employed for identifying coral categories, which can facilitate the automated processing of extensive underwater imaging data. However, these classification networks may overlook critical classification criteria like color and texture. This paper proposes a multi-local perception network (ML-Net) for image classification of healthy and bleached corals. ML-Net focuses on local features of coral targets, leveraging valuable information for image classification. Specifically, the proposed multi-branch local adaptive block extracts image details through parallel convolution kernels. Then, the proposed multi-scale local fusion block integrates features of different scales vertically, enhancing the detailed information within the deep network. Residual structures in the shallow network transmit local information with more texture and color to the deep network. Both horizontal and vertical multi-scale fusion blocks in deep networks are used to capture and retain local details. We evaluated ML-Net using six evaluation metrics on the Bleached and Unbleached Corals Classification dataset. In particular, ML-Net achieves an ACC result of 86.35, which is 4.36 higher than ResNet and 8.5 higher than ConvNext. Experimental results demonstrate the effectiveness of the proposed modules for coral classification in underwater environments.

A comparative study on hydrocarbon detection using cepstrum–based methods - Cong Tang; Kang Chen; Qing-Lin He; Long Wen; Qi Ran; Bin Luo; Jing-Hui Chang; Ya-Juan Xue (Journal of Applied Geophysics, 2024)

Unravelling solvation structure and interfacial mechanism of pyrrolidinium-based ionic liquid electrolytes in potassium-ion batteries - Xiaokang Chu; Hao Wang; Chi Hu; Qingxue Lai; Luanjie Nie; Hang Chen; Ran Chen; Zixia Lin; Mengtao Ma; Jing Zheng (Chemical Engineering Journal, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

Short-term effects of exposure to cold spells on blood pressure among adults in Nanjing, China - Tian-Lin Li; Bei-Jing Cheng; Nan Jiang; Xing-Chen Meng; Chun Wang; Yang Huang; Ke Meng; Hui Li; Xin-Yi Zhu; Ran Liu (Air Quality, Atmosphere & Health, 2024)

Experimental optimization and mechanism analysis of extracting flavonoids with the supramolecular solvents-based methods - Zhi-lu Yu; Shi-yi Hou; Li-mei Lin; Yu-ran Chu; Ya-mei Li; Zhi-min Zhang; Jing Yan; Bo-hou Xia (Sustainable Chemistry and Pharmacy, 2024)

Ecoregion-wise fractional mapping of tree functional composition in temperate mixed forests with sentinel data: Integrating time-series spectral and radar data - Ziyu Lin; K.H. Cheng; Dedi Yang; Fei Xu; Guangqin Song; Ran Meng; Jing Wang; Xiaolin Zhu; Michael Ng; Jin Wu (Remote Sensing of Environment, 2024)

The Alasu rock avalanche in the Tianshan Mountains, China: fragmentation, landforms, and kinematics - Qi-wen Lin; Yu-feng Wang; Qian-gong Cheng; Jing Huang; Hao-ran Tian; Guo-xiang Liu; Ke He (Landslides, 2024)

Circular economy strategies in supply chains, enhancing resource efficiency and sustainable development goals - Jing Qi Gao; Ding Li; Guang Hui Qiao; Qiao Ran Jia; Shi Ru Li; Han Lin Gao (Environmental Science and Pollution Research, 2024)